2015
DOI: 10.1016/j.yfrne.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic time measurement and seasonal immunological plasticity

Abstract: Seasonal variations in immunity are common in nature, and changes in day length are sufficient to trigger enhancement and suppression of immune function in many vertebrates. Drawing primarily on data from Siberian hamsters, this review describes formal and physiological aspects of the neuroendocrine regulation of seasonal changes in mammalian immunity. Photoperiod regulates immunity in a trait-specific manner, and seasonal changes in gonadal hormone secretion and thyroid hormone signaling all participate in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 161 publications
(181 reference statements)
1
52
0
Order By: Relevance
“…Importantly these results have been confirmed by other laboratories and extended by Yoshimura and others to mammals (reviews: Dardente et al, 2014;Ebling 2015;Stevenson & Prendergast, 2015) and fish (Nakane et al, 2013). Earlier I mentioned some of our studies on the role of thyroid hormones in seasonality but our efforts (38 papers) never reached the molecular level.…”
Section: The Thyroid Story: Its Molecular Basissupporting
confidence: 74%
See 2 more Smart Citations
“…Importantly these results have been confirmed by other laboratories and extended by Yoshimura and others to mammals (reviews: Dardente et al, 2014;Ebling 2015;Stevenson & Prendergast, 2015) and fish (Nakane et al, 2013). Earlier I mentioned some of our studies on the role of thyroid hormones in seasonality but our efforts (38 papers) never reached the molecular level.…”
Section: The Thyroid Story: Its Molecular Basissupporting
confidence: 74%
“…T3 is the most highly active form of the thyroid hormones and whilst the final step is still somewhat obscure it is thought that T3 then alters the end feet of glial cell elements in the median eminence, allowing increased GnRH secretion. This model is discussed by Ebling (2015) and Stevenson & Prendergast (2015) (see also Dardente et al, 2014;Wood & Loudon, 2014; and the Yoshimura papers above). In summary the thyroid story is proving fascinating but some quite difficult questions remain.…”
Section: The Thyroid Story: Its Molecular Basismentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the immune system undergoes substantial seasonal changes in gene expression, which is inverted between European locations and Oceania (7). The regulation of seasonal changes in both disease incidence and immune defense is known to interact with environmental factors, such as annual changes in day length, humidity, and ambient temperature (8). Accordingly, quantification of global spatiotemporal patterns of disease incidence can help to disentangle environmental, demographic, and physiological drivers of infectious disease transmission.…”
mentioning
confidence: 99%
“…A series of elegant timed infusion studies conducted by multiple laboratories using pinealectomised animals later revealed that duration is likely to be the key feature of the melatonin rhythm that regulates photoperiodic changes in physiology (reviewed in Bartness et al (1993)). The contrast between short duration signals in the summer and long duration winter signals is both necessary and sufficient to drive subsequent seasonal rhythms in diverse processes such as reproduction, pelage, metabolism, and immune function (Goldman 2001, Stevenson & Prendergast 2015.…”
Section: Melatonin As An Endocrine Calendarmentioning
confidence: 99%